PRAKTIK KOMUNIKASI FLEXING PUBLIK DI MEDIA - Herman Herman (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
Flexing communication is a form of symbolic interaction communication that puts pressure on image users, in practice symbols and diction have high privileges, so that the perceptions that appear are of double value. Through a case study in the form of a single descriptive form, it was found that the use of place, diction, expression, style, and intonation of the user is a form of flexing communication using symbols. So that the relationship between the communicator, the message, and the recipient becomes the main component in composing a communication message, this component influences the style of symbolic interaction that is built according to the communicator's message, the communicator's message is transmitted through the transmitter, through the message that is built then rearranged by the recipient, until it reaches the destination, at this point it is not always the same between the messages sent and those received, this is what the communicator must understand, otherwise a communication failure will occur, because in the course of the message it has the potential to be disrupted by various sources of interference that are around it.